MIKROENKAPSULASI Lactobacillus plantarum DENGAN BERBAGAI ENKAPSULAN PADA PENGERINGAN SEMPROT JUS JAMBU BIJI - Rina Ningtyas; Betty Jenie Sri Laksmi; Lilis Nuraida (Jurnal Teknologi dan Industri Pangan, 2015)
Two strains of Lactobacillus plantarum (1%) in guava juice were microencapculated by spray drying technique using several types of encapsulan, i.e. maltodextrin, enkapsulan maltodextrin combination with other materials such as gum arabic, inulin, and galaktoorigosakarida (GOS), with a ratio of 5:1. The objectives of this study were to compare the effect of encapsulation materials of Lactobacillus plantarum 2C12 and Lactobacillus plantarum BSL on heat resistance (50, 60 and 70°C), survival at low pH (2.0), bile salts (0.5%), and antimicrobial activity against Escherichia coli. Spray drying were performed at 120°C (inlet) and 70°C (outlet). The results showed that all types of encapsulation materials improved the probiotic resistancy towards heat, low pH and bile salts compared to free cells. The highest survival of probiotic cells was achieved at 50°C by maltodextrin, with the protection of 2-3 Log CFU g-1 compared to free cells. Combination of maltodextrin and GOS (5:1) showed that the highest protection toward low pH and bile salts, except for L. plantarum BSL, maltodextrin provide the best protection against bile salts. The antimicrobial activity of the cells did not change after the microencapsulation process. These results indicate that the guavapowder probiotic can be developped by microencapsulation techniques with spray drying method.